2009
DOI: 10.1111/j.1600-6143.2009.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Mesenchymal Stem Cells and Rapamycin Synergize to Attenuate Alloimmune Responses and Promote Cardiac Allograft Tolerance

Abstract: The inherent immunosuppressive properties and low immunogenicity of mesenchymal stems cells (MSCs) suggested their therapeutic potential in transplantation. We investigated whether MSCs could prolong allograft survival. Treatment involving infusion of MSCs into BALB/c recipients 24 hours after receiving a heart allograft from a C57BL/6 donor significantly abated rejection and doubled graft mean survival time compared to untreated recipients. Furthermore, combination therapy of MSCs and low-dose Rapamycin (Rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
235
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 79 publications
10
235
1
4
Order By: Relevance
“…Previous published experimental studies suggested that MSCs can, under certain conditions, induce allograft tolerance together with immunomodulatory drugs [9,10,14,19]. In our study, iPSCMSCs + Rapa treatment effectively prolonged islet allograft survival time and even induced immune tolerance in 50% of the recipients, which was consistent with results using adult MSCs with 2 mg/kg/day Rapa treatment in heart allografts [9]. Our results demonstrated that the combined treatment had synergistic effects.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Previous published experimental studies suggested that MSCs can, under certain conditions, induce allograft tolerance together with immunomodulatory drugs [9,10,14,19]. In our study, iPSCMSCs + Rapa treatment effectively prolonged islet allograft survival time and even induced immune tolerance in 50% of the recipients, which was consistent with results using adult MSCs with 2 mg/kg/day Rapa treatment in heart allografts [9]. Our results demonstrated that the combined treatment had synergistic effects.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have shown that adult MSCs alone, or combined with immunosuppressive drugs, induce allograft immune tolerance through Treg induction in vivo [8,9,17]. Berman et al first reported that infusions of donor or thirdparty MSCs reversed rejection episodes and prolonged islet function, associated with increased numbers of Tregs in peripheral blood [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed that MSCs exert potent immunosuppressive properties by reducing the surface expression of CD25, the alpha subunit of the IL-2 receptor, on T eff cells, thus blocking the IL-2 cytokine signalling pathway required for T lymphocyte activation, expansion and differentiation [8]. By targetting the detrimental alloreactive T cell response, MSCs have been shown to exhibit therapeutic potential in controlling or preventing graft rejection in many experimental animal models of organ transplantation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%